Mechanical Properties of Bamboo Through Measurement of Culm Physical Properties for Composite Fabrication of Structural Concrete Reinforcement - Javadian, Alireza; Smith, Ian F. C.; Saeidi, Nazanin; Hebel, Dirk E. (Frontiers in Materials, 2019)
Bamboo fibers with high mechanical properties can be a sustainable alternative to synthetic fibers for application in fiber reinforced polymer composites. The first aim of this study is to evaluate the dependence of mechanical properties of Dendrocalamus asper, known as bamboo Petung from Indonesia, on physical properties of the culm, including culm diameter, wall thickness, height, moisture content and specific density. Correlations between mechanical properties including tensile strength, modulus of rupture and modulus of elasticity in flexure and tension and culm physical properties have been studied. The results demonstrate that specific density is directly correlated with all these mechanical properties of bamboo while the moisture content values are correlated only with value of modules of rupture. Although wall thicknesses value of the culm are correlated with all of the mechanical properties studied, the culm diameter was only correlated with modulus of rupture and modulus of elasticity in flexure. Therefore, measurements of the culm geometry and specific density of raw bamboo have the potential for rapid, non-destructive evaluations of the quality of the bamboo, particularly in nurseries and forests where there is limited access to testing facilities. The second aim of this study is to evaluate whether such tests allow for an evaluation of the mechanical potential of the bamboo for production of high performance bamboo fiber reinforced polymer composites. Use of these formulas is illustrated through a case study of bamboo composite reinforcement for structural concrete. Pull-out tests and beam testing using this composite successfully validate the usefulness of this strategy for sustainable construction.